Konseling Kelompok Dengan Teknik Assertive Training Dalam Meningkatkan Interaksi Sosial Pada Remaja - Septasari, Dwi; Suryati, Suryati; Fitri, Hartika Utami (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
The thesis entitled "The Effectiveness of Group Counseling Using Assertive Training Techniques in Improving Social Interaction in Adolescents at the Ar Rahman Drug Rehabilitation Center Palembang". The background of this research is that there are many teenagers who are still not brave or not used to interacting with fellow teenagers and their environment, social interaction is something that is very inherent in humans as it is known that humans are social beings, therefore social interaction becomes one of the inherent characteristics of everyday human life. This thesis aims to determine the level of social interaction in adolescents and the effectiveness of group counseling with assertive training techniques in increasing social interaction in adolescents at the ar Rahman drug rehabilitation center in Palembang. The approach in this research is quantitative research with the type of experimental research in which the research design is quasi-experimental one group pretest and posttest design. The population is 30 people, where the sampling technique is by looking at the age range from 13 to 20 years, so as to get a sample of 6 people from the entire population. The instruments used in this study are through questionnaires and documentation. Data analysis used Wilcoxcon test. The results of the first study show that the level of social interaction among adolescents is in the moderate category with a percentage of 66%. The results of the Wilcoxson test show that asymp.sig (2-tailed) is worth 0.027, so it can be concluded that group counseling with assertive training techniques is effective in increasing social interaction in adolescents at the Ar-Rahman Palembang drug rehabilitation center. Which means Hₐ is accepted and Hₒ is rejected.